The Tenth Winnipeg Show. (Winnipeg : Winnipeg Art Gallery, 1966)
Deutsch, Peter ; Urquhart, Tony ; Tiessen, George ; Menses, Jan ; Warkov, Ester ; Kiyooka, Roy ; Lochhead, K.C. ; Grey, Jerry ; Pflug, Christiane ; Meredith, John ; Kiyooka, Harry ; Reichert, Don
The Tenth Winnipeg Show, Winnipeg Art Gallery, Winnipeg, November 5th to November 30th 1966
Engels
kunstcatalogus